Analisis Putusan tentang Gugatan Wanprestasi terhadap Pengingkaran Janji Kampanye oleh Presiden Terpilih - Riana Susmayanti (Universitas Islam Balitar, Blitar, 2019)
In Indonesia, the denial of campaign promises has been tried to be brought into the court. In 2009, the Indonesian Voter Institution (LPI) formally filed a lawsuit against President Susilo Bambang Yudhoyono (SBY) and Vice President M. Jusuf Kalla (JK) who failed in fulfilling campaign promises in the 2004 Presidential Election. This normative juridical research with a case study towards Central Jakarta District Court Decision No. 17 / PDT.G / 2009 / PN.JKT.PST to understand the legal reasons. The court decision was right that campaign promises do not meet the legal requirements as the agreement based on Article 1320 of the Civil Code.